Procalcitonin as a Biomarker for Bacterial Infections: Clinical Applications: Kalsitonin sebagai Biomarker untuk Infeksi Bakteri: Aplikasi Klinis - Al-Laith, Zainab Naser (Universitas Muhammadiyah Sidoarjo, 2025)
Bacterial infections can induce substantial inflammatory responses that are often mirrored by alterations in hematological parameters and serum biomarkers, such as procalcitonin. The identification of reliable biomarkers plays a critical role in facilitating early diagnosis and assessing disease severity. This study was designed to assess the diagnostic significance of serum procalcitonin levels alongside hematological indicators in patients with confirmed bacterial infections, comparing these findings with values obtained from healthy individuals. Conducted as a case-control observational study in Southern Iraq between January and April 2024, the research included 150 participants—100 with laboratory-confirmed bacterial infections and 50 healthy controls. Blood samples were collected from all participants to perform complete blood count (CBC) analysis and to determine serum procalcitonin concentrations using enzyme-linked immunosorbent assay (ELISA). Sociodemographic variables including age, gender, body mass index (BMI), and smoking status were statistically comparable between both groups. However, patients with bacterial infections showed significantly elevated procalcitonin levels (mean 5.68 ± 2.74 ng/ml) compared to controls (mean 0.39 ± 0.21 ng/ml), with a p-value of less than 0.001. Moreover, there was a direct correlation between infection severity and procalcitonin concentration. Hematological alterations in the patient group included increased white blood cell (WBC) counts, neutrophilia, lymphopenia, decreased levels of hemoglobin and hematocrit, and a marked rise in platelet counts. Interestingly, procalcitonin levels did not differ significantly by gender, suggesting that sex-based variation may not influence its diagnostic utility. These findings reinforce the clinical value of procalcitonin as a biomarker for both diagnosing bacterial infections and monitoring their severity. Additionally, associated hematological changes provide complementary information reflecting the systemic inflammatory response, thereby enhancing the effectiveness of combined biomarker-based assessment in clinical settings. Highlights: Diagnostic Value: Procalcitonin levels significantly rise in bacterial infections, making it a reliable biomarker for diagnosis and severity assessment. Clinical Correlation: A strong correlation exists between procalcitonin levels and white blood cell count, enhancing its diagnostic precision. No Gender Bias: Procalcitonin levels are consistent across genders, indicating its universal applicability in both male and female patients. Keywords: Procalcitonin, Bacterial Infection, Hematological Parameters, Inflammation, ELISA